What happens after enrollment? An analysis of the time path of racial differences in GPA and major choice - Peter Arcidiacono; Esteban M. Aucejo; Ken Spenner (IZA Journal of Labor Economics, 2012)
At the private university we analyze, the gap between white and black grade point averages falls by half between the students' freshmen and senior year. This outcome could suggest that affirmative action policies are playing a key role to reduce racial differences. However, this convergence masks two effects. First, the variance of grades given falls across time. Hence, shrinkage in the level of the gap may not imply shrinkage in the class rank gap. Second, grading standards differ across courses in different majors. We show that controlling for these two features virtually eliminates any convergence of black/white grades. In fact, black/white gpa convergence is symptomatic of dramatic shifts by blacks from initial interest in the natural sciences, engineering, and economics to majors in the humanities and social sciences. We show that natural science, engineering, and economics courses are more difficult, associated with higher study times, and have harsher grading standards; all of which translate into students with weaker academic backgrounds being less likely to choose these majors. Indeed, we show that accounting for academic background can fully account for average differences in switching behavior between blacks and whites.
Keywords: I2; I20; I23; 330; Grade inflation; Affirmative action; Major choice; Bildungsverhalten; Ethnische Gruppe; USA